THE SECRETS OF A SUCCESSFUL EDUCATION - Mukhlisa Kenjaeva (European Science Publishing, 2024)
This article is about the Education is an important in one’s life. It is the key to success in the future and to have many opportunities in our life. Education has many advantages for people. For instance, it illuminates a person’s mind and thinking. It helps students to plan for work or pursue a higher education while graduating from university. Having education in an area helps people think, feel, and behave in a way that contributes to their success, and improves not only their personal satisfaction but also their community. In addition, education develops human personality, thoughts, dealing with others and prepares people for life experiences. It makes people have a special status in their own society and everywhere they live in. I believe that everyone is entitled to have education ‘’from cradle to grave’’. There are various benefits of having education such as having a good career, having a good status in society, and having self-confidence
Keywords: article, education, key, pupil, methods.